UMPSA Professor Public Lecture Ceremony shares expertise in Future Industrial Catalyst Technologies and Sustainable Energy Storage Systems - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 5 December 2024 – The Academic and International Affairs Department (JHEAA), in collaboration with the Faculty of Industrial Sciences and Technology (FSTI), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), organised a Professor Public Lecture Ceremony at Dewan Astaka, UMPSA Gambang Campus.